Strategic Development of School With Environmental Concepts A Case Study At KharismaBangsa Bilingual Boarding School And SMAN 8 Pekanbaru - Hasan Yilmas; Zulfan Saam Auzar; Amir Awaluddin (INTERNATIONAL JOURNAL OF ECONOMICS, BUSINESS AND APPLICATIONS, 2016)
Environmental awareness is of an absolute requirement for effective environmental development efforts. Since it is closely related to the norms and ethics, environmental management by using educational path were a strategic position. Environmental education is specifically important because the world is recently experiencing imbalance (disequilibrium) state in term of environment. The present study aims at formulatingdevelopment strategies with environmental conceptson high school students. KharismaBangsa Bilingual Boarding School Tangerang and SMAN 8 Pekanbaru,which have obtained various achievements and appreciation in the environmental field, were taken as object of the study. ASWOT analysis were performed to both schools target for finding out the formulation strategy. The study suggested thatboth schools KharismaBangsa and SMAN 8 should implement an aggressive strategy, the strategy S-O (Quadrant I) which is, applied tohigh school students. It was found that the students’ awarenessincreased toward the environment whichaccordingly, were related to that support of parents, schools, and developed environmental activities with the community.